Caregivers' and Young Children's Emotional Health Needs After Pediatric Traumatic Injury. (September 2022) - Ridings, Leigh E.; Davidson, Tatiana M.; Walker, Jesse; Winkelmann, Jennifer; Anton, Margaret T.; Espeleta, Hannah C.; Nemeth, Lynne S.; Streck, Christian J.; Ruggiero, Kenneth J.
Pediatric traumatic injury (PTI) is associated with emotional health difficulties, but most US trauma centers do not adequately address emotional recovery needs. This study aimed to assess families' emotional health needs following PTI and determine how technology could be used to inform early interventions. Individual semi-structured, qualitative interviews were conducted with caregivers of children admitted to a Level I trauma center in the Southeastern United States to understand families' experiences in-hospital and post-discharge. Participants included 20 caregivers of PTI patients under age 12 ( M = 6.4 years; 70% male, 45% motor vehicle collision). Thematic analysis was used to analyze data from interviews that were conducted until saturation. Caregivers reported varying emotional needs in hospital and difficulties adjusting after discharge. Families responded enthusiastically to the potential of a technology-enhanced resource for families affected by PTI. A cost-effective, scalable intervention is needed to promote recovery and has potential for widespread pediatric hospital uptake.